PENYELESAIAN UTANG DEBITUR TERHADAP KREDITUR MELALUI KEPAILITAN - Herry Anto Simanjuntak (Universitas Quality, 2019)
In the current development of trade coupled with the rapid influence of globalization in the business world where most of the capital is a loan from various sources both from banking, investment, bond issuance and other methods that are allowed where in practice often creates many obstacles in the return of loan capital so that it needs a legal instruments that can settle these debts so as not to drag on so that the settlement can be resolved quickly, fairly, openly and effectively. The legal instrument is known through the Bankruptcy Institution. Bankruptcy Institutions are regulated in Law Number 37 of 2004 concerning Bankruptcy and Suspension and Obligations of Debt Payments, among others, the principle of Equality of Creditors ( Parity Creditorium ) regulated in Article 1 paragraph (1), article 2 paragraph (1) and article 21. The principle of debtor assets as joint collateral for creditors (pari passu prota parte) is regulated in Article 189 paragraphs (4) and (5) as well as in the explanation of article 176 letter (a). The principle of Debt Collection has the meaning as the concept of retaliation from a debtor against a bankrupt debtor by collecting his claim on the debtor's assets. This matter is regulated in Article 1 paragraph (1), article 8 paragraph (7), article 21, article 24 paragraph(2), article 65, article 69 paragraph (1), article 93 paragraph (1) and then Universal and territorial principles are regulated in Article 212, article 213 and article 214. Settlement of debtors' debts to creditors through the Court's decision is a series of processes to increase debtors on condition that the debtor has two or more creditors who do not pay off at least one debt that has fallen due and can be collected and can be proven simply in examination in the Court. And with the declared bankrupt debtor, so on can be resolved in two ways, namely by peace and bankruptcy property. Settlement by way of peace can occur if the debtor submits a peace plan and is approved by the creditor, whereas settlement by means of bankruptcy property can occur if the debtor does not propose a peace plan or propose a peace plan but is rejected by the creditor.